THE FAMILY INFLUENCE ON CHILD’S INTELLIGENCEQUOTIENT AND EDUCATION - Ann Ngozi Ugobueze (Adisam Publisher, 2025)
This study explores the significant role of family influence on a child’s intelligence quotient (IQ) and educational outcomes. It examines how various family-related factors, including genetic inheritance, socioeconomic status, parental expectations, emotional support, and cultural practices, contribute to the cognitive development and academic success of children. The research highlights the complex interplay between hereditary and environmental factors, emphasizing the importance of a supportive and enriching family environment in fostering a child’s intellectual growth. Additionally, the study discusses the challenges families face, such as economic inequalities, family instability, and the overemphasis on genetic factors, which can hinder the child’s educational potential. In addressing these challenges, the study suggests practical roles for parents in supporting their children’s education, the importance of collaboration between families and schools, and the need to overcome socio-economic barriers to enhance the educational experience. The findings underscore the necessity of strengthening family contributions to ensure that every child has the opportunity to thrive academically and intellectually.